2018
DOI: 10.1159/000484445
|View full text |Cite
|
Sign up to set email alerts
|

Liver Stiffness Measured by Two-Dimensional Shear-Wave Elastography: Prognostic Value after Radiofrequency Ablation for Hepatocellular Carcinoma

Abstract: Purpose: To evaluate the prognostic value of liver stiffness (LS) measured using two-dimensional (2D) shear-wave elastography (SWE) in patients with hepatocellular carcinoma (HCC) treated by radiofrequency ablation (RFA). Methods: The Institutional Review Board approved this retrospective study and informed consent was obtained from all patients. A total of 134 patients with up to 3 HCCs ≤5 cm who had undergone pre-procedural 2D-SWE prior to RFA treatment between January 2012 and December 2013 were enrolled. L… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
36
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(36 citation statements)
references
References 43 publications
0
36
0
Order By: Relevance
“…During the long-term follow-up after RFA for HCC, significantly negative effects on OS were found for age, prothrombin activity, advanced CTP grade, tumor size, tumor number, serum level of AFP, and the presence of porto-systemic collateral vessels 23,24,[31][32][33] . LS measured by two-dimensional shear-wave elastography has been reported as a significant predictive factor for OS after RFA for HCC 29 . However, in other studies in Korea, LS measured by TE or ARFI elastography did not have effective prediction performance for OS in HCC patients who received RFA 12,18 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…During the long-term follow-up after RFA for HCC, significantly negative effects on OS were found for age, prothrombin activity, advanced CTP grade, tumor size, tumor number, serum level of AFP, and the presence of porto-systemic collateral vessels 23,24,[31][32][33] . LS measured by two-dimensional shear-wave elastography has been reported as a significant predictive factor for OS after RFA for HCC 29 . However, in other studies in Korea, LS measured by TE or ARFI elastography did not have effective prediction performance for OS in HCC patients who received RFA 12,18 .…”
Section: Discussionmentioning
confidence: 99%
“…www.nature.com/scientificreports www.nature.com/scientificreports/ (including tumor size, number, tumor cell differentiation, vascular invasion, extra-hepatic metastasis, and serum AFP level), liver functional reserve (such as serum albumin level, platelet count, and portal hypertension), and field factors in the background liver (including the grade of hepatic inflammation and steatosis and the stage of liver fibrosis) 12,18,[25][26][27][28][29] .…”
Section: Discussionmentioning
confidence: 99%
“…Patients with LS ≥ 10kPa by 2D-SWE had a 4-fold higher risk of developing HCC than those with LS < 10 kPa. Lee et al[ 75 ] investigated the role of SWE in the prognosis of HCC after radiofrequency ablation (RFA). In 134 patients who underwent RFA as a curative treatment for HCC, LS by 2D-SWE was a significant predictor of overall survival and recurrence-free survival, and the optimal cutoff value was 13.3 kPa[ 75 ].…”
Section: Role Of 2d-swe In Predicting the Development Of Hccmentioning
confidence: 99%
“…One meta-analysis that included 1942 patients who underwent hepatic resection found that the LSM value was associated with liver-related postoperative complications, such as posthepatectomy liver failure, hepatic insufficiency and ascites [10]. Several studies have indicated that the LSM value can predict overall survival (OS) or recurrence in patients with HCC after ablation [11][12][13]; however, the results of these studies have not always been consistent.…”
Section: Introductionmentioning
confidence: 99%